Analysis of climate uniformity in indoor plant factory system with computational fluid dynamics (CFD). (August 2022) - Zhang, Ying; Kacira, Murat
Abstract : Air movement greatly affects plant growth and therefore providing adequate air movement and uniform growth environment is important. Computational fluid dynamics (CFD) simulations were applied to study transport phenomena of flow fields inside a commercial, large-scale indoor plant factory, having the goal to improve climate uniformity and subsequently crop uniformity. Five designs of ventilation system were compared with different combinations of air supply vents and return air outlets with steady-state simulation. The climate uniformity was compared with relative standard deviation (RSD) in five cases for air current speed (m s −1 ), air temperature (K), and vapour pressure deficit (Pa) at just above the top surfaces of crop canopies. These included Case 1 — with supply air inlets and return air outlets installed on opposite side walls; Case 2 — with inlets and outlets placed in alternating rows on the ceiling; Case 3 — with the same size and location of inlets as in Case 2 but with outlets placed on two side walls at the floor level; Case 4 — with perforated air tubes installed above aisles and outlets placed on the ceiling; and Case 5 — with a perforated air tube installed at each level of shelves. With the localized air ventilation method (Case 5), the climate uniformity at the crop canopy was improved compared to the control case (Case 1). The RSD for the averages of air current speed, air temperature, and vapour pressure deficit (VPD) were improved by 14.3%, 0.1%, and 1.0% respectively. Highlights: A comprehensive CFD model evaluated internal air flow and climate uniformity in a vertical farm. Various air distribution systems designs were evaluated for climate uniformity. CFD model validations with experimental data are presented. A localized air distribution design resulted in improved and uniform climate over crop canopy.